The Salient Dynamics of Cross-Border Ocean Governance in a Regional Setting: An Evaluation of Ocean Governance Systems and Institutional Frameworks in the Guinea Current Large Marine Ecosystem - Adewumi, Ibukun J.; Suárez de Vivero, Juan Luis; Iglesias-Campos, Alejandro (Frontiers in Marine Science, 2022)
This article contributes to a growing body of research on the Large Marine Ecosystems Concept. It particularly shines the light on the Guinea Current Large Marine Ecosystem (GCLME), a biodiverse maritime domain providing essential ecosystem services for the survival of a large population while at the same time under intense pressure from both anthropogenic and natural factors. With the need for coordination and cross-border ocean management and governance becoming imperative due to the magnitude of challenges and maritime domain, we examine the factors that underpin ocean governance and those key elements necessary for cross-border ocean governance cooperation in the region. The research draws on qualitative data collected from peer-reviewed literature and documents sourced from different official portals. Three countries in the region (Benin, Nigeria, and Cameroon) are selected as the descriptive and comparative case studies to examine: (i) the factors that drive ocean governance (including geographical features, maritime jurisdictions, political framework, maritime activities, and associated pressures), and (ii) key enabling factors for cross-border ocean governance and cooperation in the GCLME (including marine and coastal related policy and legal framework convergence from international to national including, and shared experiences, common issues and joint solutions). We show that the biophysical maritime features, the implementation of the United Nations Convention on the Law of the Sea (UNCLOS), otherwise known as the Law of the Sea (LOS), inherent political characteristics and the relics of colonization, and increasing ocean use and pressure on the ecosystem make ocean governance challenging in the region. Our analysis also reveals a varying level of convergence on international, regional and national legal, policy and institutional frameworks between the case studies on ocean-related aspects. Significant convergence is observed in maritime security, ocean research, and energy aspects, mostly from countries adopting international, regional and sub-regional frameworks. National level convergence is not well established as administrative and political arrangement differs from country to country in the region. These different levels of convergence help reveal procedural and operational shortcomings, strengths, weaknesses, and functional capability of countries within a cooperative ocean governance system in the region. However, experience from joint-implementation of projects, pre- and post-colonial relations between countries and the availability of transboundary organizations that have mainly emerged due to sectoral ocean challenges would play a crucial role in fostering cross-border ocean governance cooperation in the region.